2008
DOI: 10.1592/phco.28.7.843
|View full text |Cite
|
Sign up to set email alerts
|

Physician Adherence to Blood Pressure Guidelines and Its Effect on Seniors

Abstract: Overall physician adherence to blood pressure guidelines was significantly higher for the nonsenior group than for the senior group. Similarly, control of blood pressure was better in the nonsenior group. However, no significant relationship between overall adherence scores and blood pressure control was found in either group. In nonseniors, one factor grouping was significantly correlated with blood pressure control. Future studies should evaluate the process-of-care criteria to determine if and how they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…The primary aim was to evaluate if guideline adherence improved more in the intervention group than the control group, using a tool validated for this study 2123. Once the patient completed the trial, the research nurses performed a structured medical record abstraction process for all patients that included all clinic progress notes, laboratory values, medications and records from hospitalizations or emergency department visits.…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim was to evaluate if guideline adherence improved more in the intervention group than the control group, using a tool validated for this study 2123. Once the patient completed the trial, the research nurses performed a structured medical record abstraction process for all patients that included all clinic progress notes, laboratory values, medications and records from hospitalizations or emergency department visits.…”
Section: Methodsmentioning
confidence: 99%
“…9 Given the low rate of adherence, it is not surprising that only 30 to 60% of patients are at goal blood pressure. 4,6,[10][11][12][13] These data come from studies that evaluated hypertensive management in the outpatient setting. No study has evaluated adherence to hypertension guidelines or blood pressure control rates among nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…14 Evaluating adherence in this high-risk group is also important because the elderly may be less likely to receive guideline-adherent care. 13 The goal of this study was to evaluate adherence to JNC VII guidelines among nursing home residents.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that nondelayed treatment could prevent 14% of strokes and 20% of major cardiovascular events in 5 years [71]. More generally, physicians' adherence to BP guidelines is poor when patients are over 65 years of age [72]. Older patients with isolated systolic hypertension may particularly be undertreated, because many general practitioners tend to consider their BP acceptable even if systolic BP is 140 mmHg or higher, provided that diastolic BP is less than 90 mmHg [73][74][75].…”
Section: Review Casiglia Tikhonoff and Pessinamentioning
confidence: 99%